EDUTOKING: Improving the English-Speaking Skills of Grade 9 Learners using Tiktok-Based Activities - John Mark Asio; Mark Anthony Pasubillo; Christian Loid Valenzuela (Journal of English as A Foreign Language Teaching and Research, 2023)
The popularity of TikTok led the researchers to determine if its use improves the English-speaking skills of the Grade 9 students in a Science High School in Olongapo City, Philippines. The study used a descriptive-comparative research design where the researchers developed a self-assessment tool and a teacher observation checklist validated by experts in order to determine the students’ perceived English-speaking skill level. One hundred thirteen students participated in the research, and the study analyzed the data using descriptive and inferential statistics with the help of the open-source software, Jamovi. The study found no significant difference between the pretest and posttest scores of the respondents before and after integrating TikTok-based activities in their lessons using a paired sample t-test in the Jamovi software. However, for teacher-observers, the intervention is perceived as beneficial to improve the English-speaking skills of the students. The study argues that despite the popularity of TikTok amongst teenage students, it is something other than a language learning tool for students. However, the teachers observed that using the intervention can improve the English-speaking skills of the students. Overall, there is an evident disparity between the perceptions of the students and teachers regarding whether or not TikTok can have the ability to improve the English-speaking skills of the students. The researchers recommend that teachers may consider developing contextualized TikTok-based activities to make the speaking tasks more relevant and meaningful.